Systematic Review: Efforts to Increase Quality of Life For Breast Cancer Patients - Lubis, Namora Lumongga (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Background: Continuous breast cancer treatment that takes a long time can cause boredom which ultimately leads to discontinuation of therapy and even decreased quality of life. People with advanced cancer treatment show a lower quality of life than people with previous cancer and people who have never had cancer. Objective: This systematic review aims to explore alternative measures to improve the quality of life of breast cancer patients. Methods: Source search strategy from two electronic databases: CINAHL and Proquest with a limit of 2009 to 2018. The inclusion criteria used were articles relating to alternative measures to improve the quality of life of cancer patients, published online in English, having various research unit in a hospital or community. Results: From the search results, 40 articles were obtained, while those that matched the inclusion criteria were 8 articles. Based on the analysis of efforts to improve the quality of life of cancer patients. Efforts to improve the quality of life of cancer patients can be grouped into 8 actions, namely meeting spiritual needs, spiritual well-being, family support, daily activities, reflexology, health education, self-care, and alternative medicine. Conclusion: Quality of life in cancer patients can be improved by choosing an alternative course of action. If sufferers, families and health workers are committed to taking action according to the proposed procedure, it will improve the quality of life of cancer patients.Abstrak: Latar Belakang: Perawatan kanker peyudara yang berkelanjutan yang membutuhkan waktu lama dapat menyebabkan kebosanan yang pada akhirnya menyebabkan putusnya terapi dan bahkan penurunan kualitas hidup. Orang-orang dengan perawatan kanker lanjut menunjukkan kualitas hidup yang lebih rendah daripada orang-orang yang sebelumnya menderita kanker dan orang-orang yang tidak pernah menderita kanker. Tujuan: Sistematic review ini bertujuan untuk mengeksplorasi tindakan alternatif untuk meningkatkan kualitas hidup pasien kanker payudara. Metode: Strategi pencarian sumber dari dua basis data elektronik: CINAHL dan Proquest dengan batas tahun 2009 hingga 2018. Kriteria inklusi yang digunakan adalah artikel yang berkaitan dengan langkah-langkah alternatif untuk meningkatkan kualitas hidup pasien kanker, diterbitkan secara online dalam bahasa Inggris, memiliki berbagai unit penelitian di rumah sakit atau masyarakat. Hasil: Dari hasil penelusuran didapatkan 40 artikel, sedangkan yang sesuai dengan kriteria inklusi adalah 8 artikel. Berdasarkan analisis upaya untuk meningkatkan kualitas hidup pasien kanker. Upaya untuk meningkatkan kualitas hidup pasien kanker dapat dikelompokkan menjadi 8 tindakan, yaitu memenuhi kebutuhan kerohanian, kesejahteraan spiritual, dukungan keluarga, kegiatan sehari-hari, pijat refleksi, pendidikan kesehatan, perawatan diri, dan pengobatan Alternatif. Kesimpulan: Kualitas hidup pada pasien kanker dapat ditingkatkan dengan memilih satu tindakan alternatif. Jika penderita, keluarga dan petugas kesehatan berkomitmen untuk mengambil tindakan sesuai dengan prosedur yang telah diajukan, itu akan meningkatkan kualitas hidup pasien kanker.